1990
DOI: 10.1073/pnas.87.8.3185
|View full text |Cite
|
Sign up to set email alerts
|

Human monoclonal antibodies to the human immunodeficiency virus type 1 (HIV-1) transmembrane glycoprotein gp41 enhance HIV-1 infection in vitro.

Abstract: Three of 16 human monoclonal antibodies (hu-mAbs) enhanced human immunodeficiency virus type 1 (HIV-1) infection of MT-2 target cells by means ofa mechanism that is dependent on complement. Enhanced infections are characterized by an increase in cytopathic effects and antigen synthesis as well as an increase in the production of progeny virus as detected by release of reverse transcriptase activity and infectious virus into the culture medium. Analyses by radioimmunoprecipitation, Western blot, and ELISA using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Others not only fail to protect the host but even enhance infectivity. HMAbs to gp41 of human immunodeficiency virus, for example, enhance virus infection in the presence of complement (Robinson et al, 1990). Some murine MAbs to viruses including herpesviruses cross-react with uninfected human tissues, suggesting that such antibodies may be capable of causing autoimmune disease (Srinivasappa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Others not only fail to protect the host but even enhance infectivity. HMAbs to gp41 of human immunodeficiency virus, for example, enhance virus infection in the presence of complement (Robinson et al, 1990). Some murine MAbs to viruses including herpesviruses cross-react with uninfected human tissues, suggesting that such antibodies may be capable of causing autoimmune disease (Srinivasappa et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Although strong Ab responses are directed toward this region, these Abs do not neutralize the virus. On the other hand, they might enhance HIV-1 infection through a complement-mediated mechanism (53,54). Deletion of this region, therefore, could improve the immunogenicity of gp41 by diverting the Ab responses to the relatively poorly immunogenic MPER epitopes (32).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that antibodies directed to the principal immunodominant domain (PID), located in the extracellular part of the TM region, are involved in enhancement of HIV-1 infection of cell cultures in vitro (Robinson et al, 1990). The high similarity between HIV-1 and FIV PID structures (Pancino et al, 1995) suggests that this region may be involved in the induction of antibodies mediating enhancement of FIV infection.…”
Section: Discussionmentioning
confidence: 99%